Neurodegeneration in methylmalonic aciduria involves inhibition of complex II and the tricarboxylic acid cycle, and synergistically acting excitotoxicity - Okun, Jürgen G.; Hörster, Friederike; Farkas, Lilla; Feyh, Patrik; Hinz, Angela; Sauer, Sven; Hoffmann, Georg F.; Unsicker, Klaus; Mayatepek, Ertan; Kölker, Stefan (The journal of biological chemistry, 2002)
Methylmalonic acidurias are biochemically characterized by an accumulation of methylmalonate (MMA) and alternative metabolites. There is growing evidence for basal ganglia degeneration in these patients. The pathomechanisms involved are still unknown, a contribution of toxic organic acids, in particular MMA, has been suggested. Here we report that MMA induces neuronal damage in cultures of embryonic rat striatal cells at a concentration range encountered in affected patients. MMA-induced cell damage was reduced by ionotropic glutamate receptor antagonists, antioxidants, and succinate. These results suggest the involvement of secondary excitotoxic mechanisms in MMA-induced cell damage. MMA has been implicated in inhibition of respiratory chain complex II. However, MMA failed to inhibit complex II activity in submitochondrial particles from bovine heart. To unravel the mechanism underlying neuronal MMA toxicity, we investigated the formation of intracellular metabolites in MMA-loaded striatal neurons. There was a time-dependent intracellular increase in malonate, an inhibitor of complex II, and 2-methylcitrate, a compound with multiple inhibitory effects on the tricarboxylic acid cycle, suggesting their putative implication in MMA neurotoxicity. We propose that neuropathogenesis of methylmalonic aciduria may involve an inhibition of complex II and the tricarboxylic acid cycle by accumulating toxic organic acids, and synergistic secondary excitotoxic mechanisms.